Implementation of Play Method in Physical Education Learning to Improve Physical Fitness and Learning Motivation of Students - Herana, Irene; Wibowo, Sapto (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
Physical education, sports, and health are forms of education that encourage students to be actively involved through fun and interactive learning methods in order to achieve the goal of improving physical fitness and student learning motivation. This study aims to determine whether the play method has an effect on improving physical fitness and student learning motivation when applied to PJOK learning. The implementation of this research took place at SMK Negeri 2 Surabaya, Jl. Tentara Genie Pelajar No.26, Petemon Village, Sawahan District, Surabaya City, East Java. This study uses a quantitative approach. While the data collection process is carried out using tests and measurements to determine the level of fitness during the pretest and posttest and questionnaires to identify student responses to increased motivation in the pretest and posttest after the implementation of the play method. The test results were then analyzed using Descriptive tests, T tests (paired sample t-test and independent sample t-test) . Based on the results of the analysis, the results of the study on increasing physical fitness in the experimental group (Pre-Post) produced Asymp Sig. (0.001<0.05) so it is concluded that Ha is accepted and Ho is rejected which means there is a significant influence from the provision of treatment. While the learning motivation in the experimental group (Pre-Post) produces Asymp Sig. (0.000<0.05) so it is concluded that Ha is accepted and Ho is rejected which means there is a significant influence from the provision of treatment. The large influence of the application of the play method in PJOK learning on improving students' physical fitness resulted in an increase of 37.09%, and the learning motivation obtained an increase of 9.86%.